Ubristes rex sp. n., a new microdontine hoverfly from northern Brazil (Diptera: Syrphidae: Microdontinae) - Reemer, Menno (Zootaxa, 2017)
Ubristes rex sp. n., a hoverfly of the subfamily Microdontinae (Diptera: Syrphidae) is described from northern Brazil (Roraima). A diagnosis and a key are provided for distinguishing this species from the other three known species of Ubristes, which are all Neotropical. Information on distribution and habitat of all known Ubristes species is summarized. A brief comment is made on the decision to describe this species based on a single female specimen.